2017
DOI: 10.1017/s1431927617009680
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose and In-Painting Methods for (Near) Atomic Resolution STEM Imaging of Metal Organic Frameworks (MOFs)

Abstract: Metal-organic Frameworks (MOFs) are a group of crystalline and highly porous materials consisting of inorganic metal ions/clusters (nodes) that are coordinated by organic linkers. The ability to create a wide range of porous structures, where the pore size can be easily changed in size and shape offers the potential for many applications in gas storage/separation and catalysis [1]. The presence of the organic linkers or "struts" in the sample creates challenges for high resolution microscopy as the sample itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Several investigators have shown HAADF STEM images of pristine MOFs and metals in MOFs, with the MOFs including MIL-100, MIL-101 (Figure ), , MOF-5, UiO-66, ZIF-8, NU-1000, , NU-1301 (uranium) and NU-901 (bismuth) . However, the MOF structures typically degraded after exposure to only a few doses of the electron beam, leading to low-resolution images and to imaging of only primary channels.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have shown HAADF STEM images of pristine MOFs and metals in MOFs, with the MOFs including MIL-100, MIL-101 (Figure ), , MOF-5, UiO-66, ZIF-8, NU-1000, , NU-1301 (uranium) and NU-901 (bismuth) . However, the MOF structures typically degraded after exposure to only a few doses of the electron beam, leading to low-resolution images and to imaging of only primary channels.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Recently, new techniques such as HR TEM (not STEM) coupled with highly sensitive electron counting have enabled experiments with lower beam energies and, when combined with fast imaging, they have resulted in minimized sample degradation and clear images of crystalline samples with determination of local structural information (e.g., surfaces, interfaces, defects, and disorder). ,,, For example, isolated platinum atoms coordinated to oxygen atoms in MIL-100­(Cr) were observed by HR TEM, with images (Figure ) showing that the MOF structure is not highly crystalline (in contrast to many zeolites; see the amorphous structure of the MOF surface). Isolated platinum, iridium, and ruthenium atoms supported on or trapped in MOFs, or anchored on MOF nanotubes, or hosted on materials formed by pyrolysis of MOFs have been characterized by images demonstrating nearly uniform distributions of the metal.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional HRTEM is unsuitable for studying MOFs because the electron beam can easily damage their structures. High-angle annular dark-field scanning TEM has been used to observe metal clusters [28][29][30][31] and lattice distortion 28 in MOFs, but it did not disclose more structural details due to the limited resolution and weak contrast of organic components. Here, we have combined the recently developed low-dose HRTEM technique 32,33 with electron crystallography to investigate defects in MOFs by real-space direct imaging.…”
mentioning
confidence: 99%
“…We also note that mesoporous MOFs with large unit cells, such as NU-1000 and MIL-101, undergo structural shrinkage at very low doses (<10 e − Å −2 ), thereby quickly losing atomic-scale structural ordering; meanwhile, such MOFs can retain the ordered arrangement of the pores even at high doses up to more than 100 e − Å −2 . Therefore, for these MOFs, it is relatively easy to obtain images with nanometre resolution but difficult to achieve atomicresolution imaging 40,46,48,92 . The change of the diffraction pattern is commonly used as a criterion of beam damage.…”
Section: Discussionmentioning
confidence: 99%